Health literacy and self-care in patients - Rahman Panahi; Seyede Somayeh Kazemi; Afsane Karami Juyani; Malihe Pishvaei (Gonabad University of Medical Sciences, 2018)
Self-care is a process in which a patient uses his knowledge and skills to perform recommended behaviors. Therefore, patients should not only be able to obtain sufficient information about their illness and how to take care of them, they must also be able to use their knowledge in different situations and situations. In fact, patients for self-care and disease management, need to receive accurate and authoritative information to understand their condition as well as to collaborate on self-care programs [1]. Although doctors have historically been the most important source for health and medical information, but today, with the spread of media and the rapid dissemination of information through the internet, access to other resources is easy for the public. Therefore, patients' skills to achieve, accurate understanding and apply this information will have a significant effect on their health and well-being. These skills have recently been highly regarded as "health literacy" (HL) [2]. HL is defined as the level of individual capacity for gaining, interpreting, understanding basic information and health services that is necessary for a proper decision-making, and is divided into three levels of functional, communication, and critical [3]. In a meta-analysis study that summarizes the results of 85 different studies, the percentage of inadequate and marginal HL in the United States is estimated to be 25% and 20%, respectively.